Public Library Institutions and Communal Cultural Post Offices in Thai Nguyen, Nghe An, and Tra Vinh Provinces - Quỹ Châu Á; Quỹ Châu Á
From February 23rd to March 22nd 2009, The Asia Foundation (TAF), in coordination with the National Library of Vietnam (NLV) and other local partners, conducted a field survey at all 90 pilot sites, primarily located in public libraries and cultural post offices (CPOs) in the three provinces of Thai Nguyen, Nghe An and Tra Vinh to assess the training needs at provincial, district and commune levels.